Graphene nanosheets derived from plastic waste for the application of DSSCs and supercapacitors - Sandeep Pandey (Nature Portfolio, 2021)
Abstract The present study reports the upcycling process of waste plastics into value-added product graphene nanosheets (GNs) and their subsequent applications in dye sensitized solar cells (DSSCs) and supercapacitors. Bentonite nanoclay has been used as an agent for the degradation of waste plastics with two step pyrolysis processes at 450 °C and 945 °C in an inert atmosphere of N2 gas to obtain GNs. The GNs with few layers were confirmed by the RAMAN spectroscopy, XRD and HRTEM analyses. Further, FT-IR and EDX analyses also performed for the identification and quantitative analysis of functional groups in GNs. The GNs thus synthesized from plastic waste have been used for the fabrication of DSSCs and supercapacitors. The DSSC fabrication with GNs as part of photo-anode with polymeric electrolyte showed a high fill factor of 86.4% and high Voc of 0.77 V, which were also supported by the computational findings. On the other hand, the utilization of GNs as an active layer material of supercapacitor electrodes offered a high specific capacitance of 398 F/g with a scan rate of 0.005 V/s. The supercapacitor also exhibited significant energy density (Ed) and power density (Pd) of 38 Wh/kg and 1009.74 W/kg, respectively. Thus, the process illustrated the utility of waste plastics upcycling for conservation of EEE i.e., ecology, economy and energy for better tomorrow.